2020
DOI: 10.1190/geo2019-0597.1
|View full text |Cite
|
Sign up to set email alerts
|

SC-PSNET: A deep neural network for automatic P- and S-phase detection and arrival-time picker using 1C recordings

Abstract: It is important to autopick an event’s arrival time and classify the corresponding phase for seismic data processing. Traditional arrival-time picking algorithms usually need 3C seismograms to classify event phase. However, a large number of borehole seismic data sets are recorded by arrays of hydrophones or distributed acoustic sensing elements whose sensors are 1C and cannot be analyzed for particle motion or phase polarization. With the development of deep learning techniques, researchers have trie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…RNN-based networks have been used for P-wave identification (Zhu et al 2020), seismic phase association (Ross et al 2019b) and for predicting approximate earthquake times and locations (Panakkat & Adeli 2009). Model architectures based on combinations of CNN and RNN networks have been implemented for earthquake detection (Mousavi et al 2019c) and combined event detection and phase picking (Zhou et al 2019;Zheng et al 2020) tasks. Recently, novel models which apply attention mechanism on a CNN+LSTM-based network architecture (Mousavi et al 2020c) and utilize a capsule neural network (Saad & Chen 2020) have also been used for combined event detection and phase picking.…”
Section: Convolutional Layersmentioning
confidence: 99%
“…RNN-based networks have been used for P-wave identification (Zhu et al 2020), seismic phase association (Ross et al 2019b) and for predicting approximate earthquake times and locations (Panakkat & Adeli 2009). Model architectures based on combinations of CNN and RNN networks have been implemented for earthquake detection (Mousavi et al 2019c) and combined event detection and phase picking (Zhou et al 2019;Zheng et al 2020) tasks. Recently, novel models which apply attention mechanism on a CNN+LSTM-based network architecture (Mousavi et al 2020c) and utilize a capsule neural network (Saad & Chen 2020) have also been used for combined event detection and phase picking.…”
Section: Convolutional Layersmentioning
confidence: 99%
“…In SC-PSNET [29], the authors extend 3C seismograms processing with CNN to 1C seismic processing. Their study showed that CNN in combination with RNN is more promising for P-and S-detection when there are not enough training data available.…”
Section: Related Workmentioning
confidence: 99%
“…Once a machine learning (ML) model is trained, application to newly acquired fiber data, possibly even continuously, can potentially remove many bottlenecks of traditional processing. Neural networks have been shown to be successful at earthquake detection on seismometer recordings (Perol et al, 2018;Huot, Biondi, & Beroza, 2018;Zhang et al, 2019;Zheng et al, 2020). Recent studies demonstrate that they also have great potential for waveform-based event detection on continuous fiber recordings in the presence of coherent noise (Huot et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%